1994
DOI: 10.1597/1545-1569(1994)031<0008:doasor>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Strain of Rabbits with Congenital Simple Nonsyndromic Coronal Suture Synostosis Part II: Somatic and Craniofacial Growth Patterns

Abstract: In the March 1993 issue of The Cleft Palate-Craniofacial Journal we reported a female rabbit born in our laboratory with complete bilateral coronal suture (CS) synostosis. This follow-up study presents our attempts to breed the animal and establish a strain of craniosynostotic rabbits. The second part of this study presents longitudinal somatic and craniofacial growth data in offspring with coronal suture synostosis. Serial growth data from 72 animals were collected for the present study. The sample consisted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 17 publications
1
52
0
Order By: Relevance
“…Although the pathogenesis of delayed-onset synostosis is unknown, dense collagen bundles, small bony bridges, and an increased number of sutural bones have all been observed in the coronal sutures of rabbits with delayed-onset synostosis (Mooney et al, 1994a(Mooney et al, ,b, 1996aBurrows et al, 1995Burrows et al, , 1997Losken et al, 1998Losken et al, , 1999. These bundles, bridges, and supernumerary bones probably immobilize the suture and result in neurocranial growth restrictions and altered neurocapsular growth vectors, as observed in both the rabbit model (Mooney et al, 1994b;Burrows et al, 1995;Losken et al, 1998) and clinically (Reddy et al, 1990;Hoffman and Reddy, 1991;Cohen et al, 1993;Cohen and MacLean, 2000). The partially immobilized coronal sutures in rabbits from our colony usually synostose at 42-84 days of age (normal suture fusion in rabbits occurs at about 3-4 years of age (Persson et al, 1978)), as observed histologically in sham control rabbits in the present study and in previous investigations (Mooney et al, 1994b(Mooney et al, , 2002bBurrows et al, 1995;Losken et al, 1998Losken et al, , 1999.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Although the pathogenesis of delayed-onset synostosis is unknown, dense collagen bundles, small bony bridges, and an increased number of sutural bones have all been observed in the coronal sutures of rabbits with delayed-onset synostosis (Mooney et al, 1994a(Mooney et al, ,b, 1996aBurrows et al, 1995Burrows et al, , 1997Losken et al, 1998Losken et al, , 1999. These bundles, bridges, and supernumerary bones probably immobilize the suture and result in neurocranial growth restrictions and altered neurocapsular growth vectors, as observed in both the rabbit model (Mooney et al, 1994b;Burrows et al, 1995;Losken et al, 1998) and clinically (Reddy et al, 1990;Hoffman and Reddy, 1991;Cohen et al, 1993;Cohen and MacLean, 2000). The partially immobilized coronal sutures in rabbits from our colony usually synostose at 42-84 days of age (normal suture fusion in rabbits occurs at about 3-4 years of age (Persson et al, 1978)), as observed histologically in sham control rabbits in the present study and in previous investigations (Mooney et al, 1994b(Mooney et al, , 2002bBurrows et al, 1995;Losken et al, 1998Losken et al, , 1999.…”
Section: Discussionmentioning
confidence: 97%
“…1) at 10 days of age and the quantitative assessment of coronal suture growth from serial radiographs (Mooney et al, 1994b(Mooney et al, , 1996aBurrows et al, 1995;Losken et al, 1998Losken et al, , 1999. Cephalographs of the rabbits were taken at 10 and 25 days of age, and rabbits in which coronal suture marker separation fell below the 95% confidence interval of the mean for unaffected rabbits were classified as having delayed-onset synostosis.…”
Section: Surgerymentioning
confidence: 99%
See 3 more Smart Citations